Migration Shocks and Housing: Short-Run Impact of the Syrian Refugee Crisis in Jordan - Ibrahim Alhawarin; Ragui Assaad; Ahmed Elsayed (Institute of Labor Economics (IZA), 2020)
This paper investigates the impact of migration shocks on housing conditions and rental prices for the local population. The identification comes from the regional variation in the large influx of Syrian refugees to Jordan in the wake of the Syrian conflict which started in 2011. Combining detailed household-level surveys with information on where Syrian refugees are concentrated, we employ a difference-in-difference approach and show that the influx had negative impacts on housing quality and increased the rents paid by local households. Residential mobility also increased in response to the flow of refugees, and this could have acted as a channel through which housing quality decreased and may have attenuated the impact on rents. The effects are more pronounced among poorer and less-educated households, those who are arguably in competition with refugees for housing.
Keywords: O18; R21; R23; 330; migration; Syrian refugee crisis; housing; Jordan